Gwadar-Kashgar Economic Corridor: Challenges and Imperatives for Pakistan and China - Saima Perveen; Jehanzeb Khalil (Journal of Political Studies, 2015)
Gawadar Port is a great strategic asset for Pakistan. Coupled with the natural deep sea port, geo-strategic importance of its location, dependency of land locked CARs/ China and changing international nexus in the region has increased the importance of establishing Gwadar-Kashgar Economic Corridor (GKEC) to accrue maximum benefits and strengthen strategic partnerships with regional powers. GKEC is perhaps a project, which has tremendous potential for future economic uplift and strategic partnerships for Pakistan. The Kashgar-Gwadar Economic Corridor (KGEC) has capacity to generate economic revival for Pakistan and prosperity in the western region of China. This paper will analyze some very important questions like what is geostrategic importance of Gwadar-Kashgar Economic Corridor? What are challenges for Pakistan and China in development of this economic corridor? It will describe imperatives for Pakistan and China as well. GKEC will prove to be a game changer on regional canvas and is expected to bring prosperity and improved quality of life in general to region and in particular to Pakistan. There is a dire need to take on board all the regional and global players by addressing their concerns for early establishment of GKEC.